2010
DOI: 10.1088/0957-0233/21/5/055703
|View full text |Cite
|
Sign up to set email alerts
|

Stress measurement using magnetic Barkhausen noise and metal magnetic memory testing

Abstract: This paper describes a new compound magnetic testing system using magnetic Barkhausen Noise (BN) and Metal Magnetic Memory (MMM) testing technique for stress measurement. BN has become an important nondestructive technique due to its exceptional material and stress characterization capabilities. MMM is recently developed technique with special ability for defect detection, stress detection and stress history record capacity. In the applied tensile experiment, BN and MMM signal were acquired via BN measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…The impedance of coil is dependent on factors such as the gap between the sensor coil and the test specimen h , the resistivity of the test specimen ρ , the magnetic permeability of the test specimen μ and the frequency of the excitation signal f [23][24][25][26].…”
Section: Lrc Modelmentioning
confidence: 99%
“…The impedance of coil is dependent on factors such as the gap between the sensor coil and the test specimen h , the resistivity of the test specimen ρ , the magnetic permeability of the test specimen μ and the frequency of the excitation signal f [23][24][25][26].…”
Section: Lrc Modelmentioning
confidence: 99%
“…al. [18] is presented in Figure 1. The linear dependence in the elastic region is completely sufficient, because rail geometry deformation emerges earlier than plastic deformation in the axial direction of the rail [18].…”
Section: Metal Magnetic Memory Measurementmentioning
confidence: 99%
“…Method on internal rail stress measurement seem like a research that has not been done yet. As mentioned in Section 5, this method does not require external magnetization [18] and this is a great asset for possible further application. If the measurement of the gradient of magnetic flux in rail results in a similar dependence as shown in Figure 1, the potential of applicability of this method would be great [18].…”
Section: Further Research Orientationmentioning
confidence: 99%
“…Jiles, Atherton, and Sablik 6 have demonstrated that hysteresis behavior of polycrystalline materials can be derived using the model of magnetic moments interacting with the effective field. Hence, magnetization of a bulk magnetic body can be calculated from the following equation…”
Section: Magnetic-plastic Modelmentioning
confidence: 99%
“…The magnetic properties in this stage are affected by the following factors. [5][6][7][8][9] (1) The density of dislocation considerably increases with an increase of plastic deformation of materials. The contributions of the interaction between dislocation and domain magnetization play an important role in the changes of magnetic properties.…”
mentioning
confidence: 99%